2019
DOI: 10.2147/ijn.s190954
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Nanosilver/poly (DL-lactic-co-glycolic acid) on titanium implant surfaces for the enhancement of antibacterial properties and osteoinductivity</p>

Abstract: Background: Despite titanium (Ti) implants have been commonly used in the medical device field due to their superior biocompatibility, implant-associated bacterial infection remains a major clinical complication. Nanosilver, an effective antibacterial agent against a wide spectrum of bacterial strains, with a low-resistance potential, has attracted much interest too. Incorporation of nanosilver on Ti implants may be a promising approach to prevent biofilm formation. Purpose: The objective of the study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…52 Both Yunzhu Qian et al and Xuemin Zeng et al reported that the silver-modified implants, of which the total concentration of Ag + was below 0.06ppm and 0.12ppm, had the ability to promote cells proliferation and osteogenesis. 12,52 To eliminate the toxic effects of AgNPs on cellular proliferation, we loaded ultra-low-concentration of AgNPs (about 0.2ppm released at the first 24h) on TiO 2 nanotubes as mentioned above ( Figure 1F), which had no significant cytotoxicity by CCK-8 test ( Figure 2C). Besides, we also used the culture medium containing different concentration of AgNPs (0, 0.05, 0.10, 0.20, 0.50 and 2.0ppm) to treat macrophages ( Figure S1C).…”
Section: Cell Morphology and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Both Yunzhu Qian et al and Xuemin Zeng et al reported that the silver-modified implants, of which the total concentration of Ag + was below 0.06ppm and 0.12ppm, had the ability to promote cells proliferation and osteogenesis. 12,52 To eliminate the toxic effects of AgNPs on cellular proliferation, we loaded ultra-low-concentration of AgNPs (about 0.2ppm released at the first 24h) on TiO 2 nanotubes as mentioned above ( Figure 1F), which had no significant cytotoxicity by CCK-8 test ( Figure 2C). Besides, we also used the culture medium containing different concentration of AgNPs (0, 0.05, 0.10, 0.20, 0.50 and 2.0ppm) to treat macrophages ( Figure S1C).…”
Section: Cell Morphology and Proliferationmentioning
confidence: 99%
“…8,9 Besides, Ag@TiO 2 -NTs with a lower initial concentration (0.14ppm) of Ag + ions also achieved an excellent synergistic antibacterial capacity in combination with antibiotics both in vitro and in vivo. 10 Interestingly, it has recently been reported that the AgNPs-loaded biomaterials with continuing releasing extremely low dose Ag + could enhance cell adhesion, 10 spreading, 11 proliferation, 12 reactive oxygen species (ROS) scavenging, 11 and new bone formation 13 by the unique controlled-release characteristic and topographic feature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the unmodified PEEK is less osteoconductive and bioactive than Ti (Najeeb et al, 2016). A nanosilver/polymer-coated Ti implant was studied by Zeng et al and it exhibited excellent antibacterial and osteoinductive activities (Zeng et al, 2019). A nanosilver/polymer-coated Ti implant was studied by Zeng et al and it exhibited excellent antibacterial and osteoinductive activities (Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the hybrid materials that best integrate those contributions will be a new trend in optimizing the design of implants. A nanosilver/polymer-coated Ti implant was studied by Zeng et al and it exhibited excellent antibacterial and osteoinductive activities (Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the studies (95%) were conducted in vitro and mainly against cultured human osteoblast and fibroblast cell lines (48%) as well as cultured mouse osteoblast cell line (MC3T3-E1) (33%). [35] conducted in vivo analyses to qualify biocompatibility and biocidal aspects using rabbits while [32] performed in vivo antibacterial assay using male rats. A total of 17 (81%) studies examined the antimicrobial ability of NPs along with the biocompatibility evaluations.…”
Section: Study Characteristicsmentioning
confidence: 99%